The Effect of Exercise on Mental Health: Coping with Stress and Anxiety Through Physical Activity (Systematic literature review) - Putra, Reno Yuzar Eka; Barlian, Eri; Neldi, Hendri; Yendrizal; Rahman, Dally; Zarya, Fiky (Poltekkes Kemenkes Palu, 2024)
This study is a systematic review that aims to evaluate the effect of exercise on mental health, especially in overcoming stress and anxiety. By reviewing a number of studies selected through strict inclusion and exclusion criteria, the review gathered data from a variety of sources including peer-reviewed journals, articles. The data analysis method used is meta-analysis. The results showed that physical activity can significantly reduce symptoms of stress and anxiety. This applies to different types of sports, from aerobics, yoga, to strength training. This therapeutic effect is associated with the release of endorphins and other neurotransmitters that play a role in improving mood and reducing tension. In addition, exercise also improves sleep quality and aids in the regulation of circadian rhythms, which directly affect the management of stress and anxiety. The study also found that exercise intensity and duration played a role in its tiveness. Light to moderate exercise, performed regularly, is more effective in reducing symptoms of stress and anxiety compared to sporadic high-intensity exercise. Consistency and continuity in exercise routines prove to be more important than the intensity of exercise performed. However, the study also acknowledged variations in individual responses to exercise. Factors such as age, gender, initial health conditions, and personal preference for the type of exercise can affect how effective exercise is at coping with stress and anxiety in a particular individual. Taken together, these findings provide strong evidence supporting the use of exercise as a non-pharmacological strategy in managing stress and anxiety. The study encourages health practitioners to recommend exercise as an integral part of mental health treatment plans, as well as suggesting further research to explore specific mechanisms behind the psychological benefits of physical activity.